1983
DOI: 10.1099/0022-1317-64-3-613
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Neutral Oligosaccharides in Mature Sindbis Virus Glycoproteins are Synthesized from Truncated Precursor Oligosaccharides in Chinese Hamster Ovary Cells

Abstract: SUMMARYWe have previously demonstrated the presence of unusual small asparaginyloligosaccharides [(Man)3 GIcNAc2-ASN] in the mature glycoproteins of Sindbis virus released from both wild-type and lectin-resistant Chinese hamster ovary cells, but the mechanism of synthesis of these structures was not determined. Gel filtration and endo-fl-N-acetylglucosaminidase analyses of Pronase-digested glycopeptides from [3H]mannose-labelled Sindbis virus released at different times after infection of a phytohaemagglutinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The glycosylation of a-Toga virus envelope proteins has been studied in vertebrate [10,15,22,25,26,[35][36][37]48] and in invertebrate [6,7,18,48] cells. In all cases, all types of Asn-tinked oligosaccharides are believed to be the product of a common precursor glycan transferred cotranslationally from dolichyl-P-P-glycan [18,22,32,43].…”
Section: Introductionmentioning
confidence: 99%
“…The glycosylation of a-Toga virus envelope proteins has been studied in vertebrate [10,15,22,25,26,[35][36][37]48] and in invertebrate [6,7,18,48] cells. In all cases, all types of Asn-tinked oligosaccharides are believed to be the product of a common precursor glycan transferred cotranslationally from dolichyl-P-P-glycan [18,22,32,43].…”
Section: Introductionmentioning
confidence: 99%
“…For example, we cannot exclude a possibility of a protein glycosylation bottleneck, which might be essential for a stable S protein maturation. In this regard, it has been demonstrated that Sindbis virus infection of Chinese hamster ovary cells substantially altered the protein glycosylation processes of infected cells, with both abnormal truncated oligosaccharides and normal full-sized oligosaccharides being transferred from lipid-linked precursors to newly synthesized viral glycoproteins [ 41 ]. Furthermore, glucose starvation leads to a severe under glycosylation of viral glycoproteins, with some glycosylation sites not acquiring covalently linked oligosaccharides [ 42 ].…”
Section: Discussionmentioning
confidence: 99%